Manajemen Implementasi Moderasi Beragama Dalam Kurikulum Merdeka Pada Pembelajaran PAI di SD - Khusaini, Ahmad Alfin; Inayati, Ummi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
The purpose of this study is to explain how the Management of Implementation of Religious Moderation in the Independent Curriculum for Islamic Education Learning in Elementary Schools. This research is a literature study. Data collection uses some relevant literature. The results of this study are the management of the implementation of religious moderation in the independent curriculum in PAI and BP learning in elementary schools, there needs to be proper management through: 1) planning, namely planning what moderation values ​​can be collaborated with the selection of materials in accordance with the independent curriculum, 2) implementation, namely applying the value of moderation in accordance with the material in accordance with the teaching module in the independent curriculum, 3) controlling, namely controlling the level of conformity of the implementation of religious moderation in the independent curriculum and 4) evaluating. So that it can run well in accordance with the learning objectives and desired learning outcomes. Keywords: Religious Moderation, Independent Curriculum, PAI Learning